2020
DOI: 10.1111/trf.16017
|View full text |Cite
|
Sign up to set email alerts
|

Donor‐dependent aging of young and old red blood cell subpopulations: Metabolic and functional heterogeneity

Abstract: Background: Characteristics of red blood cells (RBCs) are influenced by donor variability. This study assessed quality and metabolomic variables of RBC subpopulations of varied biologic age in red blood cell concentrates (RCCs) from male and female donors to evaluate their contribution to the storage lesion. Study Design and Methods: Red blood cell concentrates from healthy male (n = 6) and female (n = 4) donors were Percoll separated into less dense ("young", Y-RCCs) and dense ("old", O-RCCs) subpopulations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
48
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 70 publications
(116 reference statements)
4
48
1
Order By: Relevance
“…As such, these results support a model of accelerated RBC aging in vivo caused by persistent exercise, which would result in accelerated removal from circulation of RBCs with limited functional capability. The resultant shorter RBC circulatory lifespans would require enhanced erythropoiesis to generate a population of younger cells that are better equipped to face oxidant challenges, at least in the case of aging in vivo [77,78] and in vitro [79] in a subject age-and gender-dependent fashion [80,81]. Future studies should focus on understanding whether exercise training itself can also generate more robust RBCs that are able to cope with a "harsher" environment.…”
Section: Discussionmentioning
confidence: 99%
“…As such, these results support a model of accelerated RBC aging in vivo caused by persistent exercise, which would result in accelerated removal from circulation of RBCs with limited functional capability. The resultant shorter RBC circulatory lifespans would require enhanced erythropoiesis to generate a population of younger cells that are better equipped to face oxidant challenges, at least in the case of aging in vivo [77,78] and in vitro [79] in a subject age-and gender-dependent fashion [80,81]. Future studies should focus on understanding whether exercise training itself can also generate more robust RBCs that are able to cope with a "harsher" environment.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, there is both plausible biologic rationale and mounting evidence that suggest (1) there is significant donor‐based and process‐based variation in ‘chronologic’ and ‘physiologic’ age accrual (e.g., not all RBC units ‘age’ at the same rate) 86,87 and (2) ‘physiologic’ rather than ‘chronologic’ age principally determines relative risk and benefit for transfusion of RBC units of differing quality 88 . One such example could be represented by donors with G6PD deficiency, whose RBCs – even fresh – are incapable of activating the HMP and thus would phenocopy the observations we reported here for end of storage RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, sex and the age of the donors in this study were unknown. Consequently, these important variables (i.e., sex, age, and lifestyle), which can impact storage lesion development, 87 remain unaccounted herein. Despite these limitations, this work specifically defines progression of storage‐associated energy failure in RBCs, with biologically plausible links to the well‐characterized physiologic and biophysical features of the RBC storage lesion, while also enhancing our understanding of the molecular mechanisms that preserve native RBC function.…”
Section: Discussionmentioning
confidence: 99%
“… 7 However, these results, as well as those of other groups were mainly obtained from pRBC of male donors, or the sex of donors was not specified. 5 , 8 Recently, it has also been suggested that RBC from females are less prone to storage lesion and age slower than male erythrocytes 9 , 10 but these reports were mainly focused on metabolic and functional RBC analysis.…”
mentioning
confidence: 99%